Projected changes in atmospheric rivers affecting Europe in CMIP5 models - Alexandre M. Ramos; Ricardo Tomé; Ricardo M. Trigo; Margarida L. R. Liberato; Joaquim G. Pinto (Geophysical Research Letters)
Abstract Atmospheric Rivers (ARs) are elongated bands of high water vapor concentration extending to the midlatitudes, which can be associated with intense precipitation and floods over continental areas. We analyze ARs reaching Europe in simulations from six Coupled Model Intercomparison Project Phase 5 (CMIP5) global climate models (GCMs) to quantify possible changes during the current century, with emphasis in five western European prone coastal areas. ARs are represented reasonably well in GCMs for recent climate conditions (1980–2005). Increased vertically integrated horizontal water transport is found for 2074–2099 (RCP4.5 and RCP8.5) compared to 1980–2005, while the number of ARs is projected to double on average for the same period. These changes are robust between models and are associated with higher air temperatures and thus enhanced atmospheric moisture content, together with higher precipitation associated with extratropical cyclones. This suggests an increased risk of intense precipitation and floods along the Atlantic European Coasts from the Iberian Peninsula to Scandinavia.